SINKING OF FOREIGN SHIPS IN INDONESIAN TERRITORIAL WATERS AS AN IMPLEMENTATION OF PENANCE LAWS AND INTERNATIONAL LAW - Lea Juliana (Awang Long Law Review, 2021)
Indonesia's geographical territory as an archipelago with a large territorial area of water, so Indonesia has great potentialin the results of its marine resources. This led to the arrival of many foreign fishing boats that passed within the territoryof Indonesia's Exclusive Economic Zone to catch illegal fishing. Illegal fishing that occurs in Indonesia territorial watersresulted in heavy losses. The management and utilization of fish resources in the territorial waters of the State of Indonesia makes it necessary to be supervised by the supervisory task force created by Presidential Regulation No. 115 of 2015. About the Illegal Fishing Eradication Control Unit. As well as surveillance efforts that the Government ofIndonesia in combating illegal fishing with the Indonesian Ministry of Marine Affairs by sinking this ship aims toprovide a deterrent effect. Foreign actors or ships. This has been regulated in Law No. 45 of 2009 on Fisheries. Sinkingof ships in Indonesia in judicial procedures can be done also by assessingthe court process and accompanied by clear evidence. Sanctions for the sinking of foreign ships within Indonesian territorial waters against Indonesia's positivelaws, as well as the linkage of judicial proceedings to the sinking of ships with the law penance and international law. Sinkingforeign ships is a form of application of penance law from sistem Indonesian criminal law, as well as related in Hukum International. Metode yuri research in normative, with comparison of Indonesian law with law in othercountries, namely the Illegal Fishing Law of Malaysia Act 317 and the joint rules Eu countries against foreign ships.The sinking of foreign-flagged vessels that violate Indonesian territorial waters is part of Indonesia's penance laws.